Analysis of Energy Consumption of Indonesian Flat Glass Industry PT. X Based on Green Industry Standards - Revitasari Reviana; Heru Susanto Bambang (MATEC Web of Conferences, 2018)
The natural resource consumption is higher along with the increasing needs of people in various sectors, which affect the environment directly or indirectly. Especially for energy consumption, the supply and availability of fossil energy, as a non-renewable energy, are increasingly depleted and not guaranteed in the long run, coupled with the issue of emissions generated. The industrial sector as a driver of the national economy, including the flat glass industry as a case study, is an energy intensive sector. Almost 83% of its energy consumption used for operating the furnaces as the main production unit with temperature up to 1700 °C continuously about 15 years. The increasing of effectiveness and efficiency of energy consumption in the glass manufacturing process will affect significantly to sustainable production in PT. X and gives many other valuable impacts to the economic growth, environment, and society. So, this study analyzes about the energy consumption in PT. X based on Green Industry Standards, believed as a proper strategy, the benchmark of some standards or related regulations for energy consumption in several countries, and the opportunity of the green industry concept implementation in the glass manufacturing process. The methods were studied of literature, plant observation, interview, and data calculation manually and using spreadsheets. The results indicate that the Flat Glass Industry PT. X requires the improvement to increase the effectiveness and efficiency of energy consumption to get the sustainable production.